THE ANALYSIS ECRANISATION OF PETER’S CHARATERIZATION AFFECTED BY HIS CONFLICTS IN THE NOVEL AND IN THE FILM ENTITLED THE CHRONICLES OF NARNIA: PRINCE CASPIAN - Charima, Deasmabella (Universitas Gunadarma, 2020)
This research aims at analyzing the process of ecranisation in the main character’s conflicts and characteristics, Peter Pevensie, that occurs in the novel and the film. The reason for using conflict is because to know the character’s characteristics can be seen from the way he deals with his conflicts. The data were taken from the novel The Chronicles of Narnia: Prince Caspian by C.S Lewis and film The Chronicles of Narnia: Prince Caspian by Andrew Adamson, because there are numerous differences, among them are Peter’s conflicts and characteristics. The descriptive qualitative method is applied in this research. The results of this research show the process of ecranisation is reduction, addition, and variation. The process of ecranisation found psychological conflict, social conflict, and physical conflict. But the physical conflict did not find in variation. The main character’s characteristics appeared in the novel comprise of wise, firm, responsible, and big-hearted. Whereas in the film the main character’s characteristics describe as stubborn, arrogant, irritable, doubtful, wise, persistent, cautious, and big-hearted.